Hydrocarbons preserved in a 2.7 Ga outcrop sample from the Fortescue Group, Pilbara Craton, Western Australia. Issue 2 (13th November 2014) - Hoshino, Y.; Flannery, D. T.; Walter, M. R.; George, S. C.
Abstract The hydrocarbons preserved in an Archean rock were extracted, and their composition and distribution in consecutive slices from the outside to the inside of the rock were examined. The 2.7 Ga rock was collected from the Fortescue Group in the Pilbara region, Western Australia. The bitumen I (solvent‐extracted rock) and bitumen II (solvent‐extracted hydrochloric acid‐treated rock) fractions have different hydrocarbon compositions. Bitumen I contains only trace amounts of aliphatic hydrocarbons and virtually no aromatic hydrocarbons. In contrast, bitumen II contains abundant aliphatic and aromatic hydrocarbons. The difference seems to reflect the weathering history and preservational environment of the investigated rock. Aliphatic hydrocarbons in bitumen I are considered to be mainly from later hydrocarbon inputs, after initial deposition and burial, and are therefore not indigenous. The lack of aromatic hydrocarbons in bitumen I suggests a severe weathering environment since uplift and exposure of the rock at the Earth's surface in the Cenozoic. On the other hand, the high abundance of aromatic hydrocarbons in bitumen II suggests that bitumen II hydrocarbons have been physically isolated from removal by their encapsulation within carbonate minerals. The richness of aromatic hydrocarbons and the relative scarcity of aliphatic hydrocarbons may reflect the original compositions of organic materials biosynthesised in ancient organisms in the Archean era, or the high thermal maturity of the rock. Cyanobacterial biomarkers were observed in the surficial slices of the rock, which may indicate that endolithic cyanobacteria inhabited the surface outcrop. The distribution of aliphatic and aromatic hydrocarbons implies a high thermal maturity, which is consistent with the lack of any specific biomarkers, such as hopanes and steranes, and the prehnite–pumpellyite facies metamorphic grade.